2018
DOI: 10.3389/fpsyt.2018.00353
|View full text |Cite
|
Sign up to set email alerts
|

Partnership Satisfaction in Living Kidney Donors

Abstract: Due to organ shortage, living kidney donation is gaining increasing importance. Medical progress enables a successful transplantation between unrelated individuals, even individuals with AB0-incompatibilities. Spouses are the largest group of living kidney donors. The aim of this study was to assess partnership status and partnership satisfaction in living kidney donors. In the cross-sectional study we investigated 361 living kidney donors. The time since donation ranged between 1 and 38 years. The partnership… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…This study suggests that family functioning differs depending on relative type. Donors with interspousal LKT have higher partnership satisfaction than donors with nonspousal LKT (Nöhre et al, 2018). It is possible that differences in family formation affect family dynamics (e.g., parents and children are related by birth, whereas spouses are related by marriage).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study suggests that family functioning differs depending on relative type. Donors with interspousal LKT have higher partnership satisfaction than donors with nonspousal LKT (Nöhre et al, 2018). It is possible that differences in family formation affect family dynamics (e.g., parents and children are related by birth, whereas spouses are related by marriage).…”
Section: Discussionmentioning
confidence: 99%
“…A thematic synthesis of qualitative studies found that the recipient will also have living kidney transplantation (LKT)-specific feelings toward their family, such as feeling the burden of obligation to receive a kidney from a family member (Ralph et al, 2017). Some studies in Western countries have focused only on the donor–recipient relationship after LKT (Nöhre et al, 2018; Ralph et al, 2017). However, these methods for assessing the pretransplant relationship after transplantation cannot rule out the influence of recall bias.…”
mentioning
confidence: 99%
“…13 Nöhre et al showed a higher partnership satisfaction among spousal donors compared to non-spousal donors. 14 Another study highlighted that single and divorced men's lack of social support may represent an obstacle to work resumption following living kidney donation. 15 Our study cannot allow us to explore this finding, but the literature shows a link between a good donation experience and being the recipient's partner.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the donor‐recipient relationship as a protector to loss to follow up, a study has shown a link between getting married and a higher chance of getting transplanted 13 . Nöhre et al showed a higher partnership satisfaction among spousal donors compared to non‐spousal donors 14 . Another study highlighted that single and divorced men's lack of social support may represent an obstacle to work resumption following living kidney donation 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Living-donor transplantation represents an alternative—not a substitution—to the waiting list for a deceased donor organ. Nevertheless, living transplant often is the only treatment option to improve or save the life of patients with an end-stage kidney failure ( 18 ). It is well known that living-donor organ transplants are associated with fewer complications than cadaver transplants, a better outcome, and a longer survival time of the donor organ ( 7 , 17 , 18 ).…”
Section: Discussionmentioning
confidence: 99%